THE PATTERNS OF SEX DETERMINATION AND DIFFERENTIATION GENES IN GREEN SEA TURTLE (Chelonia mydas) - Anggraini Barlian; Noviana Vanawati; Fitria D. Ayuningtyas (The East Java Biological Society, 2015)
Green sea turtle (C. mydas) is one of TSD (Temperature-dependent Sex Determination, TSD) animals which mean that their sex is determined by the egg’s incubation temperature. Genotypic Sex Determination (GSD) homologous genes play a role in TSD process. Until now, research on the pattern of sex determination genes in C.mydas has not been conducted yet. The aim of this research is to reveal sex determination and differentiation genes expression in Mesonephros-Gonad (MG) complexes of C. mydas embryos which incubated in masculinizing temperature (MT) and feminizing temperature (FT). C. mydas eggs were incubated in 3 different stage of TSP (Thermosensitive Period) at masculinizing temperature (26±10C, MT) and feminizing temperature (31±10C FT). Mesonefros-gonad complexes were isolated at Pre-TSP stage (FT at 14th day, MT at 24th day), TSP stage (FT at 24th day, MT at 36th day) and differentiated stage (FT at 40th day, MT at 58th day). RNA from mesonephros-gonad (MG) complexes were converted into cDNA by RT-PCR process. Pattern of Sf1, Wt1, Aromatase, FoxL2, Sox9, Wnt4, Fgf9 and Rspo1 genes expression were analyzed by quantitative Real Time PCR (qPCR) method with β-actin gene as an internal control. Result of this study shown that expression pattern of Sf1, Wt1, Aromatase, FoxL2, Sox9, Wnt4, Fgf9, and Rspo1genes in gonadal embryo of C. mydas were increased during gonadal development stage. Four genes expression patterns (Wnt4, Fgf9, Rspo1, and FoxL2) have shown that these genes have role in sexual differentiation rather than in sexual determination.